Ticket to perform: an explorative study of trainees’ engagement in and transfer of surgical training - Sigurd Beier Sloth; Rune Dall Jensen; Mikkel Seyer-Hansen; Gunter De Win; Mette Krogh Christensen (BMC Medical Education, 2023)
Abstract Background Research suggests that simulation-based surgical skills training translates into improved operating room performance. Previous studies have predominantly focused on training methods and design and subsequent assessable performances and outcomes in the operating room, which only covers some aspects of training engagement and transfer of training. The purpose of this qualitative study was to contribute to the existing body of literature by exploring characteristics of first-year trainees’ engagement in and perceptions of transfer of surgical skills training. Methods We conducted an explorative study based on individual interviews with first-year trainees in General Surgery, Urology, and Gynaecology and Obstetrics who participated in a laparoscopic skills training program. Informants were interviewed during and two months after the training program. A thematic cross-case analysis was conducted using systematic text condensation. Results We interviewed 12 informants, which produced 24 transcripts for analysis. We identified four main themes: (1) sportification of training, (2) modes of orientation, (3) transferrable skills, and (4) transfer opportunities. Informants described their surgical training using sports analogies of competition, timing, and step-by-step approaches. Visual orientations, kinaesthetic experiences, and elicited dialogues characterised training processes and engagement. These characteristics were identified in both the simulated and the clinical environment. Experiences of specific skills transfer included ambidexterity, coordination, instrument handling, and visuospatial ability. General transfer experiences were salient in informants’ altered training approaches. Informants considered the simulation-based training an entry ticket to perform in the operating room and mentioned supervisor-trainee relationships and opportunities in the workplace as critical conditions of transfer. Conclusions Our findings elucidate characteristics of surgical training engagement that can be interpreted as self-regulated learning processes that transcend surgical training environments. Despite appreciating the immediate skills improvements resulting from training, trainees’ narratives reflected a struggle to transfer their training to the clinical setting. Tensions existed between perceptions of transferable skills and experiences of transfer within the clinical work environments. These results resonate with research emphasising the importance of the work environment in the transfer process. Our findings provide insights that may inform the development of training programs that support self-regulated learning and transfer of training from the simulated to the clinical environment.